14 Relation of Low Serum Magnesium Level with Type-2 Diabetes Mellitus in Eastern India - Subhash Chandra; Sahu Sarada Prasad; Swaim Rakesh Keshari; Ratan Kireet (Dr. Annil Mahajan, 2022)
Background: Odisha, a state in eastern India is swiftly becoming one among the diabetes hotspots in the country. Magnesium deficiency is implicated in poor glycemic status and various complications of diabetes. However, prevalence of hypomagnesemia is wide-ranging and its association with micro-vascular complications is contradictory. Purpose: To estimate the prevalence of hypomagnesemia in type 2 diabetes and determine its association with microvascular complications and glycemic status. Methods: A cross-sectional study was conducted on 165 type 2 diabetic patients. HbA1c was measured by HPLC method and serum Mg2+ was measured by colorimetric method. Serum Mg2+ level of <1.7mg/dl was defined as hypomagnesemia. Results: Hypomagnesemia was found in 12.1% (n=20) of patients. Retinopathy and microalbuminuria were found as 40% vs. 35.8 % and 30% vs. 20% between hypomagnesemia and normomagnesemia groups, respectively. Patients with poor glycemic control were more susceptible to have hypomagnesemia (16.5% vs. 3.5%) (OR: 5.314, 95% CI: 1.193-23.915, p=0.016). Moreover, HbA1c had significant inverse relation with serum Mg2+ (r= -0.3, p<0.001). Conclusion: Strict glycemic control or increased dietary intake of magnesium may decline the incidence of hypomagnesemia in diabetic patients.